Agronomic performance and nutritive value of millet silages (Acta Scientiarum. Animal Sciences, 2017)
The objective of this study was to assess agronomic characteristics and nutritional values of silages of millet genotypes. Planting was done in randomized blocks, with five replicates per genotype. Green matter yield for genotypes ADR 500 and CMS 01 was higher and similar to each other, with 40.16 and 41.36 t ha (p > 0.05). There was no significant difference for dry matter yield, with the mean being 9.93 t ha (p > 0.05). The silages were similar (p > 0.05) as to pH, Aw and N-NH3/TN, presenting values of 3.92, 0.97 and 7.64%, respectively. There were no significant differences (p > 0.05) concerning the bromatological composition of the silages of the different genotypes, with a mean of 30.74% of dry matter, 10.21% for crude protein and 58.69% for neutral detergent fiber (p > 0.05). The dry matter digestibility mean stood at 59.90%. Based on the nutritional values and digestibility of the millet silages, the five genotypes are suitable for silage production, with potential for the North of Minas Gerais.